2022
DOI: 10.1177/20563051221077308
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying Counter-Public Spheres on Social Media: News Sharing of Alternative Versus Traditional Media After the 2019 Chilean Uprising

Abstract: While much research exists on the role of digital media use in protest movements, few studies compare the long-term impact of protests on online use of alternative and mainstream digital media. This holds particularly true in countries of the global south. Our study addresses this knowledge gap by examining the massive demonstrations that occurred in Chile on 18 October 2019. Based on data from 1,221,487 Facebook posts from 31 media outlets collected 10 months before and after the protests, we detected signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
0
5
0
1
Order By: Relevance
“…Meanwhile, alternative media sources experienced a more lasting shock. This boost helped alternative, online outlets to counter mainstream narratives, causing public opinion “to question traditional media and its coverage of the riots, social unrest, and police repression and human rights abuses” ( Luna et al, 2022 , p. 2). In some traditional outlets, the scope of disruption and repression caused journalists to question more detached approaches to the production of news content, leading some to adopt an “epistemic mode where journalists validate the decision to take a position in the conflict, which in the uprising was a commitment to stories of police abuse and human rights violations” ( Orchard and Fergnani, 2022 , p. 12).…”
Section: Determinants Of Perceptions Of Human Rights Violationsmentioning
confidence: 99%
“…Meanwhile, alternative media sources experienced a more lasting shock. This boost helped alternative, online outlets to counter mainstream narratives, causing public opinion “to question traditional media and its coverage of the riots, social unrest, and police repression and human rights abuses” ( Luna et al, 2022 , p. 2). In some traditional outlets, the scope of disruption and repression caused journalists to question more detached approaches to the production of news content, leading some to adopt an “epistemic mode where journalists validate the decision to take a position in the conflict, which in the uprising was a commitment to stories of police abuse and human rights violations” ( Orchard and Fergnani, 2022 , p. 12).…”
Section: Determinants Of Perceptions Of Human Rights Violationsmentioning
confidence: 99%
“…Another study by Wang et al that considered trustworthy and untrustworthy news sources instead of mainstream versus alternative ones arrived at a similar result and suggested that small communities can become extremely effective in pushing news stories to other communities [ 21 ]. Another relevant contribution to the existing evidence was made by Luna et al who highlighted the differences in the dissemination of mainstream versus alternative media on Facebook: while alternative news content sharing was steadily increasing with time after the publication, mainstream news content sharing, in contrast, followed a burst and decay pattern [ 22 ]. Despite the existing evidence, little is known about the impact of alternative media content on the dynamics of discussions in fringe communities and whether such content reinforces or even produces more negative attitudes and narratives about the discussion topics.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, alternative media tend to represent ideas from the extreme sides of the political spectrum. During the country's last episodes of social unrest, analysts have said that alternative media even aligned with protesters' and social movements' demands (Luna et al, 2022). While alternative news sources used to be considered not as professional-or not as objective-as traditional news outlets (in Chile but also elsewhere, as explained by Holt et al, 2019), alternative media are nowadays considered a legitimate source of information, reaching high peaks of popularity and news consumption in the country (Newman et al, 2021), especially after Chile's political riots in October 2019, when they reached a sustained growth in audience (Luna et al, 2022).…”
Section: The Alternative/legacy Dichotomy In Chile's News Media Lands...mentioning
confidence: 99%